Short-term performance peaking in an elite cross-country mountain biker - Rønnestad, B. R.; Hansen, J.; Vegge, G.; Mujika, I. (Journal of Sports Sciences, 2014)
Endurance athletes usually achieve performance peaks with 2-4 weeks of overload training followed by 1-3weeks of tapering. With a tight competition schedule, this may not be appropriate. This case investigates the effect of a 7-day overload period including daily high-intensity aerobic training followed by a 5-day step taper between two competitions in an elite cross-country mountain biker. Pre-test peak oxygen consumption was 89 ml/kg·min, peak aerobic power 6.8 W/kg, power output at 2 mmol/L blood lactate concentration 3.9 W/kg, maximal isometric force 180 Nm and squat jump 21 cm. During overload, perceived leg well-being went from normal to very heavy. On day 1 after overload, vastus lateralis and vastus medialis EMGmean activity was reduced by 3% and 7%, respectively. Other baseline measurements were reduced by 3-7%. On day 4 of the taper, he felt that his legs were good and all measurements were 3-7% higher than before overload. On day 6 after the taper, his legs felt very good. This case shows that an elite mountain biker (11th in UCI World Cup one week prior to the pre-test) could achieve a rather large supercompensation by using a 12-day performance peaking protocol.